Eyewitness Evidence Obtained with the Self‐Administered Interview© Is Unaffected by Stress. Issue 1 (26th September 2015) - Krix, Alana C.; Sauerland, Melanie; Raymaekers, Linsey H. C.; Memon, Amina; Quaedflieg, Conny W. E. M.; Smeets, Tom
Summary: The Self‐Administered Interview© (SAI) serves to elicit eyewitness statements directly after the crime. Witnesses could still experience stress then. Because stress during retrieval produces memory‐impairing effects, this study sought to compare the SAI with free recall under stress. An interaction between stress and interview was expected such that the SAI would elicit more comprehensive accounts than free recall in the control, but not in the stress group. One hundred and twenty‐seven participants underwent a stress or control task. They witnessed a live staged crime and completed an SAI or a free recall. The SAI elicited a higher number of correct verifiable event details and a higher number of correct and incorrect perpetrator details than free recall. Accuracy rates were unaffected. Unexpectedly, despite causing moderate stress‐induced cortisol elevations, stress exposure did not influence memory performance and did not interact with interview type. Hence, the SAI can safely be used, when witnesses are moderately stressed.Copyright © 2015 John Wiley & Sons, Ltd.